2004
DOI: 10.1007/s00401-003-0810-2
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma cells release factors that disrupt blood-brain barrier features

Abstract: The blood-brain barrier (BBB), mediated by endothelial tight junctions, is defective in malignant gliomas such as glioblastoma, resulting in cerebral edema and contrast enhancement upon neuroradiological examination. The mechanisms underlying BBB breakdown are essentially unknown. Since non-neoplastic astrocytes are required to induce BBB features of cerebral endothelial cells, it is conceivable that malignant astrocytes have lost this ability due to dedifferentiation. Alternatively, glioma cells might activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 30 publications
5
101
0
1
Order By: Relevance
“…The integrity of the compound is expected to be stable during the cell assays described herein. Although there was no observed penetration of the blood brain barrier in these normal healthy mice, there could still be penetration in a glioma setting in which the blood brain barrier may be compromised (23), and this compound could provide a good starting point for further optimization to improve drug-like properties and potency.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the compound is expected to be stable during the cell assays described herein. Although there was no observed penetration of the blood brain barrier in these normal healthy mice, there could still be penetration in a glioma setting in which the blood brain barrier may be compromised (23), and this compound could provide a good starting point for further optimization to improve drug-like properties and potency.…”
Section: Discussionmentioning
confidence: 99%
“…Like most solid tumors, gliomas express and secrete vascular endothelial growth factor/vascular permeability factor (VEGF/VPF) that induces proliferation and migration of neighboring endothelial cells [32][33][34][35][36]. Remodeling of the BBB vasculature by VEGF disrupts the formation of tight junctions, increases vascular permeability (VP), and results in a disordered vasculature characteristic of tumor-induced angiogenesis [34,[37][38][39]. Our previous studies have demonstrated that the non-receptor tyrosine kinase, Src, is essential for the maintenance of the BBB [40].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our intravenous injection of the Q-GSCT peptide into tumor-bearing mice reveals that this peptide can easily penetrate brain tumor-blood barriers and specifically accumulate in tumor tissues by targeting Nestin-positive GSCs, although the underlying mechanism remains to be clarified. However, we infer that the ability of GSCT peptide to penetrate tumor vessels would be attributable to its low molecular weight [24] and the looseness of the tumor bloodebrain barrier [25,26].…”
Section: Discussionmentioning
confidence: 99%